Nitrogen effects on Striga hermonthica infestation, grain yield and agronomic traits of tolerant and susceptible maize hybrids - Kim, S.K.; Adetimirin, Victor O.; Akintunde, A.Y. (Wiley, 1997)
phytoparasite, Striga hermonthica (Del.) Benth., infests millions of hectares of cultivated fields of cereal crops in sub-Saharan Africa. Yield losses are often 70 but can be as high as 100% and farmers often abandon infested fields and move to new areas. The objectives of this study were to investigate the effects of nitrogen on S. hermonthica infestation and the subsequent grain yield and agronomic traits of tolerant and susceptible maize hybrids (Zea mays L.). Two tolerant and two susceptible hybrids were grown under six levels of N (0–150 kg ha−1), with and without Striga seed infestation. The trials were conducted for 3 yr at Mokwa, Nigeria. Each plant was infested with approximately 3000 germinable Striga seeds, and the density of Striga that emerged, Striga damage on the host plant, plant height, stalk lodging, and grain yield were measured. Striga infestation (emergence and host damage), maize grain yield, and plant height were significantly affected by N rates. Two tolerant hybrids showed significantly lower Striga emergence and host plant damage symptoms than the susceptible hybrids (P< 0.001). Interactions between infested and uninfested plots and hybrid (tolerant vs. susceptible) for grain yields and stalk lodging were significant (P < 0.001). Striga infestation reduced grain yields of two susceptible hybrids by 49%, and of two tolerant hybrids by 24%. The two tolerant hybrids produced on average 87% greater grain yields than the two susceptible hybrids under low N rates (0– 60 kg ha−1) and 51% greater yields under high N (90–150 kg ha−1). Among the plant traits measured, Striga damage score had the highest correlation with grain yield (r = − 0.60**)